A comparative study of burnout syndrome among health professionals in a Nigerian teaching hospital (2003)
Burnout as a measure of stress has generated research interest in the past two decades. However, there is a dearth of research on this interesting and important phenomenon in Nigeria. This study compared burnout and its associated factors in various health professionals working at the University College Hospital, Ibadan, Nigeria. Two hundred and sixty health care providers were sampled from 5 main units: Theatre/Intensive Care Unit (ICU), Accident and Emergency (A & E), Oncology, Dentistry and General Outpatients Department (GOP), among others. Included were 104 nurses (40%), 83 doctors (31.9%), 21 pharmacists/pharmacy technicians (8.0%), 10 medical social workers (3.8%) and 42 nursing assistants (16.1%). Outcome measures included the Maslach Burnout Inventory (MBI), the 30-item General Health Questionnaire (GHQ) and the Spielberger State Trait Anxiety Inventory (STAI). Core findings indicated that nurses consistently reported higher scores on all measures of burnout: exhaustion (F = 3.60, df= 258, P <.05); accomplishment (F = 3.94, df=258, P < .05) and depersonalization (F = 4.58, df258, P < .01) when compared with other health care providers. Significant differences were also noted between nurses and all other care provider, in total scores on the General Health Questionnaire (F = 6.54, df 258, P < .01) and the State Trait Anxiety Inventory (F = 1.91, df 258, P <.05), respectively. These results are discussed in relation to the existing literature on burnout in Nigeria. Further empirical study is highly suggested in view of dearth of studies on the occupational health of health care providers in Nigeria.